Proceedings of the Seventh International Conference on Information and Communication Technologies and Development 2015
DOI: 10.1145/2737856.2738024
|View full text |Cite
|
Sign up to set email alerts
|

The creation of capital through an ICT-based learning program

Abstract: Massive Open Online Courses (MOOCs) have recently received a great deal of attention from both researchers and the general public. Their free, open nature allows global access, including by individuals in developing countries. This study will explore ways in which MOOCs can be used as tools for development in these underprivileged areas. Using data collected through interviews with facilitators and students participating in a US State Department program, we apply and extend Bourdieu's framework of cultural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…MOOCs have also been applied to developing contexts for their promise of free education and increasing access for underprivileged students. Most MOOCs are created with a Western, educated, industrialized, rich, and democratic (WEIRD [18]) audience in mind, but some researchers have found that deploying MOOCs abroad can provide tangential benefits in the form of cultural and social capital [26]. However, the mismatch of assumptions between the course content and local context can be barriers to MOOC adoption [25], and it is uncommon for MOOC students to participate as an alternative to an unaffordable formal education [12].…”
Section: Related Workmentioning
confidence: 99%
“…MOOCs have also been applied to developing contexts for their promise of free education and increasing access for underprivileged students. Most MOOCs are created with a Western, educated, industrialized, rich, and democratic (WEIRD [18]) audience in mind, but some researchers have found that deploying MOOCs abroad can provide tangential benefits in the form of cultural and social capital [26]. However, the mismatch of assumptions between the course content and local context can be barriers to MOOC adoption [25], and it is uncommon for MOOC students to participate as an alternative to an unaffordable formal education [12].…”
Section: Related Workmentioning
confidence: 99%
“…Many MOOC formats may simply repackage old, didactic pedagogies (Chadaj et al, 2015;Onah, Sinclair, Boyatt & Foss, 2014), and "freemium" xMOOC models, where basic content is free but premium features cost extra, can result in sub-optimal experiences for Southern learners (Kalman, 2014). Observers have noted a shift from teacher-to learner-centred pedagogy in OER (Kanwar, Kodhandaraman, & Umar, 2010), while some suggest that MOOCs need to encourage more problem-based (Ally & Samaka, 2013;Maitland & Obeysekare, 2015) and project-based learning (Nkuyubwatsi, 2014).These approaches can, however, sometimes be met with resistance (Liyanagunawardena & Williams, 2015), and participants may not trust new, unfamiliar online learning platforms (Garrido et al, 2016) or may be wary of commenting on course forums (Kizilcec et al, 2017;Onah et al, 2014).…”
Section: Online Pedagogiesmentioning
confidence: 99%
“…Nkuyubwatsi (2014) identifies benefits in local collaborative study groups, and the "meetup" function on some MOOC platforms encourages learner interaction offline (Bulger, Bright, & Cobo, 2015). "MOOC camps" run by the U.S. State Department help learner groups to access courses while being mentored by English-speaking embassy staff (Godwin-Jones, 2014; Maitland & Obeysekare, 2015;Wildavsky, 2014), similar to the MOOC+ model of peer-supported learning (Adams, Liyanagunawardena, Rassool, & Williams, 2013).…”
Section: Online Pedagogiesmentioning
confidence: 99%
“…formation of local communities of practice (Firmansyah & Timmis, 2016). Maitland and Obeysekare (2015) argue that MOOC study groups allow participants to accumulate cultural and cultural capital in and through the facilitated MOOC experience.…”
Section: Introductionmentioning
confidence: 99%